(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As a result of the COVID-19 outbreak, schools throughout the globe have been forced tocancel classes. In order to maintain their academic programs, most universities and colleges have begunusing online learning platforms. For a developing nation like India, where technological limits likesuitable devices and bandwidth availability presents a severe barrier, the concerns concerning thereadiness, designing, and efficacy of e-learning are still not completely understood. In this surveyresearch, 307 students from the field of agriculture were asked about their thoughts on and preferencesfor online education. To aid in the development of an efficient virtual classroom, we also investigatedstudent preferences for a variety of features. Seventy percent of respondents mentioned they wouldconsider taking courses online to help with curriculum management during the outbreak. Most pupilsfavored using their smartphones as educational tools. Content analysis revealed that students wouldbenefit most from having each class session videotaped and ending with a quiz. Students think thatonline courses are appealing because of their adaptability and convenience, but that lack of internetaccess in remote locations is a barrier to participation in online learning programs. While a totaltransition to online mode may not be feasible in the agricultural education system, as many courses arepractice-oriented, the insights from this article might be useful in creating the curriculum for the newnormal.